A complementation assay for in vivo protein structure/function analysis in Physcomitrella patens (Funariaceae)1. (14th July 2015) - Scavuzzo‐Duggan, Tess R.; Chaves, Arielle M.; Roberts, Alison W.
Abstract : Premise of the study: A method for rapid in vivo functional analysis of engineered proteins was developed using Physcomitrella patens . Methods and Results: A complementation assay was designed for testing structure/function relationships in cellulose synthase (CESA) proteins. The components of the assay include (1) construction of test vectors that drive expression of epitope‐tagged PpCESA5 carrying engineered mutations, (2) transformation of a ppcesa5 knockout line that fails to produce gametophores with test and control vectors, (3) scoring the stable transformants for gametophore production, (4) statistical analysis comparing complementation rates for test vectors to positive and negative control vectors, and (5) analysis of transgenic protein expression by Western blotting. The assay distinguished mutations that generate fully functional, nonfunctional, and partially functional proteins. Conclusions: Compared with existing methods for in vivo testing of protein function, this complementation assay provides a rapid method for investigating protein structure/function relationships in plants.